Ageing, social participation, and everyday mobility – Facilitating age-friendly environments - Gustav López Svensson; Vanessa Stjernborg (Journal of Urban Mobility)
Due to the increasing share of older people worldwide, the United Nations has directed an initiative towards a ''decade of healthy ageing'' to promote ''age-friendly environments''. This study aims to gain a deeper understanding of how to promote social participation and everyday mobility in later life. The ambition is to increase the knowledge about how to create more age-friendly environments and social inclusion – for everyone. The study focuses on a social centre for older people in the municipality of Trelleborg in the south of Sweden. The social centre is located in an area with several retirement homes and hosts a variety of opportunities for social interaction for older people in combination with other services. The municipality also arranges free excursions for older people in the municipality departing from the social centre. Another initiative is a pilot project testing an autonomous bus outside of the social centre to ordinary public transport. The study includes observations, interviews with older people and officials, as well as travel-alongs. The results show that a combination of social participation and mobility can facilitate a more active everyday life for older people, increase social connectedness, and contribute to the creation of age-friendly environments.